2018
DOI: 10.1002/smll.201801852
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Switchable Fullerene‐Based Synergy Therapy for Alzheimer's Disease

Abstract: C has a special dual function; it can act as both a powerful reactive oxygen species (ROS) producer under UV or visible light and an ROS scavenger in the dark. However, ROS has double-edged effects in living systems. It is still a great challenge for biomedical application to switch and adjust the two opposite properties of C in one system. Herein, UCNP@C -pep (UCNP: upconversion nanoparticle, pep: Aβ-target peptide KLVFF) is designed as a near-infrared-switchable nanoplatform for synergy therapy of Alzheimer'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 51 publications
(39 reference statements)
1
94
0
Order By: Relevance
“…53,54 Photo-oxygenating Ab is capable of disintegrating Ab aggregates through increasing the protein polarity, which is an attractive strategy for AD therapy. [55][56][57][58] However, in the presence of Cu, just oxygenating Ab may not entirely block its brillation because Cu can still promote protein aggregation by coordinating to Ab. Considering that Cu and Ab are two critical pathogenic factors of AD, 59,60 we envisioned that in situ synthesized bifunctional drug agent with Ab-oxygenating and Cu-chelating properties could effectively disassemble Ab-Cu aggregates in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…53,54 Photo-oxygenating Ab is capable of disintegrating Ab aggregates through increasing the protein polarity, which is an attractive strategy for AD therapy. [55][56][57][58] However, in the presence of Cu, just oxygenating Ab may not entirely block its brillation because Cu can still promote protein aggregation by coordinating to Ab. Considering that Cu and Ab are two critical pathogenic factors of AD, 59,60 we envisioned that in situ synthesized bifunctional drug agent with Ab-oxygenating and Cu-chelating properties could effectively disassemble Ab-Cu aggregates in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that photooxygenation decreased Ab40 brillation and, possibly, toxicity, through increasing protein polarity. 56 The inhibition effect of compound 6 on Cu-accelerated Ab40 aggregation was then evaluated. Aer UV light (1 W cm À2 ) irradiation for 1 h, Ab40 monomer (10 mM) and Cu (10 mM) were incubated with 2 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…Nanozymes are new articial enzymes in the combined eld of nanomaterials and enzymology research that aimed to design novel and efficient enzymatic mimics. [1][2][3] Until now, a variety of nanomaterials have been used to mimic the activity of naturally occurring enzymes, [4][5][6][7][8] such as nanocarbon materials, [9][10][11] fullerene, 12 carbon nitride, 13 Fe 3 O 4 nanoparticles, 14 mesoporous silica nanoparticles, 15 dopamine nanoparticles, 16 melanin nanoparticles, 17 and metal-organic complexes. 18 Noble metalbased nanomaterials have also shown signicant advantages as enzyme mimetics; 19,20 gold nanoparticles (AuNPs) possess excellent stability, good biocompatibility, ease of functionalization, and unique optical, and surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…This dual property of fullerenes to either quench or generate cell-damaging ROS has been applied as a cytoprotective or cytotoxic anticancer/antimicrobial/anti-Ab agent. [22][23][24][25][26] Previous reports indicated that fullerenes, and certain fullerene derivatives, inhibit Ab aggregation much more efficiently under photo-irradiation with visible light. 24,25 The dual property of C 60 to either scavenge or produce ROS has been used for a synergistic therapy for Alzheimer's disease (AD).…”
Section: Introductionmentioning
confidence: 99%
“…24,25 The dual property of C 60 to either scavenge or produce ROS has been used for a synergistic therapy for Alzheimer's disease (AD). 26 Fullerenes have two important advantages in AD research: their structure allows them to cross the blood-brain barrier 27 and they show a high capacity to inhibit Ab bril formation. 16,17,24,25,[28][29][30] However, there is controversy regarding the biocompatibility of fullerenes: some groups report nontoxic effects in different tested models, such as the LLC-PK1 proximal tubule cell model 31 or L929 mouse subcutaneous connective cells; 32 however, a high concentration of fullerenes induces toxicity in the same studies.…”
Section: Introductionmentioning
confidence: 99%